On the Need to Include Representatives of Religion in the Activities of Institutions of the Penal System - ABEUOV, Dulat (Journal of Advanced Research in Law and Economics, 2018)
In this article, the features of the behavior of a person convicted to serving a sentence with isolation from society in places of deprivation of liberty and ways of its possible radicalization are considered. Given the social characteristics, moral and psychological properties and features of the inner world of the individual, which is distinguished by moral and philosophical disorientation, psychological and educational methods of work of the staff of the penal system for preparing a convict for life at liberty are indicated. In this regard, the positive experience of countries such as England, the Czech Republic, Estonia, and Russia is considered and measures for educational influence in penitentiary institutions on convicts are suggested, one of which is the introduction of prison chaplains in order to exclude the radicalization of the convict.